KEPRIBADIAN TOKOH UTAMA DALAM NOVEL PRINI SANTIKA ROMANTIKA DALAM GELAP) KARYA YURINDA HART - Mela, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this study was to describe the personality of the main character in the novel Prini Santika (Romance in the Dark) by Yurinda Hart. The problems in this study included the description of the personality aspect of the main character, the factors behind the emergence of the personality aspect of the main character, and the plan of personality implementation of the main character in the novel Prini Santika (Romantika in the Dark) in learning Indonesian. The method in this research is descriptive qualitative method with psychoanalytic approach. Based on the results of the research, there is a conclusion that the combination of personality aspects that influenced by (1) ego, (2) id and ego, (3) id and superego, (4) ego and superego, (5) id, ego, and superego. Factors behind the emergence of aspects of personality include; Biological factors, curious motives, love motives, self-esteem motives and the need to seek identity, motives for values, attitudes, and emotions. The results of this research can be implemented in Indonesian language learning based on the 2013 curriculum in the XII class of SMA about analyzing the history of stories, news, advertisements, editorial/opinion, and fiction stories in the novel both through oral and written. Keywords: personality, character, factor, psychoanalysis